Nutrient requirements of dairy cattle revised - James R. Dunham (Kansas Agricultural Experiment Station Research Reports, 1988)
The 1988 National Research Council's (NRC) Nutrient Requirements of Dairy Cattle have been revised. Adjustments have been made in the recommended requirements for net energy for lactation (NEL); crude protein (CP); calcium (Ca); phosphorus (P); and vitamins A, D, and E. In addition, suggestions are made for using undegraded intake protein (UIP) and degraded intake protein (DIP) for diet formulation.; Dairy Day, 1988, Kansas State University, Manhattan, KS, 1988;
Keywords: Kansas Agricultural Experiment Station contribution; no. 89-107-S; Dairy; Nutrient requirement; Crude Protein; Calcium; Phosphorus; Vitamins; Energy